Preparation method of magnesium-lithium alloy plasma electrolytic oxidation film layer in pure ionic liquid
By using pure ionic liquid on the surface of magnesium lithium alloy for plasma electrolytic oxidation, the problems of high energy consumption and membrane defects in traditional technology have been solved, and high efficiency and low cost corrosion resistance have been achieved, and magnesium lithium alloys have been expanded in aviation. Applications in aerospace and other fields.
Patent Information
- Application Number
- CN202411378649.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional plasma electrolytic oxidation technology has high energy consumption, high cost and micropores and microcracks inside the membrane layer in the treatment of magnesium lithium alloys, which limits its widespread use in industrial applications.
Use pure ionic liquid as electrolyte to perform plasma electrolytic oxidation in a normal temperature and non-aqueous environment. Through constant current mode and appropriate process parameters, a uniform and dense film layer is formed, reducing or eliminating pores in the film layer and improving magnesium lithium Corrosion resistance of alloy.
It significantly reduces the working voltage of plasma electrolytic oxidation, improves energy efficiency, forms a film with high corrosion resistance and low density, enhances the corrosion resistance of magnesium lithium alloys, and expands its application in aerospace and other fields.
Smart Images

Figure CN119194559A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium-lithium alloy electrolytic coating, and in particular to a method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid. Background Art
[0002] Plasma electrolytic oxidation, also known as micro-arc oxidation, is a new environmentally friendly surface modification technology developed from traditional anodizing technology. It refers to the use of arc discharge to enhance and activate the reaction occurring at the anode, thereby forming a high-quality reinforced ceramic film on the surface of samples made of aluminum, titanium, magnesium and other metals and their alloys. By applying voltage to the sample with a dedicated plasma electrolytic oxidation power supply, the metal on the surface of the sample interacts with the electrolyte solution, forming a micro-arc discharge on the surface of the sample, and under the action of high temperature, electric field and other factors, a ceramic film is formed on the metal surface, thereby achieving the purpose of sample surface strengthening.
[0003] The film layer prepared by plasma electrolytic oxidation has good bonding with the substrate, greatly improving the surface hardness of the material, and the film layer has good wear resistance, heat resistance, corrosion resistance and good insulation performance, overcoming the limitations of metals such as aluminum, titanium, magnesium and their alloys in application. This technology has the characteristics of simple operation and controllable film layer function, simple process and low environmental pollution. It is a new green and environmentally friendly material surface treatment technology with broad application prospects in aerospace, machinery, electronics, decoration and other fields.
[0004] As the lightest metal structural material, magnesium-lithium alloy has high specific strength and specific stiffness, good electrical and thermal conductivity, excellent anti-electromagnetic interference and biocompatibility. It has important application value and broad application prospects in the fields of automobile, aerospace, electronics, biomedicine, etc. However, poor corrosion resistance is one of the main obstacles limiting its widespread application in industrial products. Many researchers have tried to perform plasma electrolytic oxidation surface treatment. Studies have shown that plasma electrolytic oxidation treatment is an effective strategy to enhance the corrosion resistance of magnesium-lithium alloys.
[0005] However, the use of conventional plasma electrolytic oxidation in industrial applications is greatly limited, mainly due to the high energy consumption and high cost of the technology. When treating magnesium-lithium alloys, plasma electrolytic oxidation technology usually uses voltages as high as 400~500V. In order to expand the application scope of plasma electrolytic oxidation and improve its energy efficiency, there are currently two main strategies to reduce energy consumption. One is to reduce the operating voltage during plasma electrolytic oxidation treatment, and the other is to accelerate the growth rate of the ceramic film layer. The main methods include pretreatment, adjusting power output parameters, changing electrolyte composition, and changing electrolyte concentration ratio.
[0006] Another factor that limits the application of plasma electrolytic oxidation is the presence of micropores and microcracks inside the plasma electrolytic oxidation film, which increases the penetration channels of corrosive media during the corrosion process, thereby damaging the protective performance of the underlying substrate.
[0007] Therefore, it is imperative to improve the corrosion resistance of the plasma electrolytic oxide film, which can be achieved through a variety of methods, including changing the electrolyte, pretreatment and sealing treatment. In addition, in order to improve the corrosion resistance and obtain an oxide film without any undesirable elements, some researchers have innovatively proposed plasma electrolytic oxidation surface treatment in molten salt, such as plasma electrolytic oxidation at 280°C using a NaNO3-KNO3 molten salt system on the surface of aluminum alloy or titanium alloy; plasma electrolytic oxidation (plasma electrolytic fluorination) using an NH4HF system at 150°C on the surface of magnesium-lithium alloy. Plasma electrolytic oxidation is carried out using a high-temperature molten salt system. During the operation, the electrolyte does not need to be cooled and the film growth rate is high. The film structure is uniform, the film composition is simple, and non-oxides can be generated. However, there are also some limitations, such as the heating system increases energy consumption, the high temperature environment has high requirements for the experimental device, the molten salt system is easy to corrode the experimental device, and the experimental operation safety is low. Summary of the invention
[0008] The present invention provides a method for preparing a magnesium-lithium alloy plasma electrolytic oxidation film layer in a pure ionic liquid. From the perspective of lightweight, a magnesium-lithium alloy is selected as a matrix, and a normal temperature non-aqueous electrolyte is used for plasma electrolytic oxidation, breaking the limitation of a high-temperature molten salt system and realizing non-aqueous electrolyte plasma electrolytic oxidation under low temperature conditions. The electrolyte has a simple composition and strong conductivity, and can improve current efficiency and oxidation rate. The prepared film layer is uniform, dense, fine and smooth, and has strong bonding with the matrix, so as to solve the technical problems that the existing method for preparing a magnesium-lithium alloy plasma electrolytic oxidation film layer needs to be carried out under high temperature conditions, is easy to corrode experimental equipment, and has high energy consumption.
[0009] The present invention provides a method for preparing a magnesium-lithium alloy plasma electrolytic oxidation film layer in a pure ionic liquid, comprising the following steps: S100, subjecting a magnesium-lithium alloy sample to plasma electrolytic oxidation surface treatment, using the magnesium-lithium alloy sample as an anode, stainless steel, graphite or titanium as a cathode, and pure ionic liquid as a plasma electrolytic oxidation electrolyte, and adopting a constant current mode to perform plasma electrolytic oxidation in a normal temperature non-aqueous environment.
[0010] Furthermore, the pure ionic liquid is one of 1,3-dimethylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butylimidazolium tetrafluoroborate, and N-butylimidazolium.
[0011] Furthermore, a magnesium-lithium alloy corrosion inhibitor suitable for magnesium-lithium alloy is added to the plasma electrolytic oxidation electrolyte. After adding the corrosion inhibitor, the plasma electrolytic oxidation electrolyte is placed in a stirring state or an ultrasonic state until the corrosion inhibitor is completely dissolved.
[0012] Furthermore, the magnesium-lithium alloy corrosion inhibitor is at least one of azole compounds, organic phosphates, and rare earth salts.
[0013] Furthermore, the process parameters of the plasma electrolytic oxidation in step S100 are: using a constant current mode, maintaining the temperature below 40° C., the plasma electrolytic oxidation time is 10 to 30 minutes, the frequency is 600 to 1000 Hz, and the forward duty cycle is 12% to 20%.
[0014] Furthermore, before step S100, a pre-treatment step is also included, specifically: S10, grinding the surface of the magnesium-lithium alloy sample until it is smooth and free of impurities; S20, degreasing the ground magnesium-lithium alloy sample to remove oil stains on the surface of the magnesium-lithium alloy sample; S30, cleaning the surface of the magnesium-lithium alloy sample and drying it.
[0015] Furthermore, the process parameters for degreasing in step S20 are: the degreasing solution is a mixed solution consisting of 2-50 g / L of sodium hydroxide, 0-20 g / L of sodium silicate, 1-10 g / L of sodium carbonate, and 0-30 g / L of sodium phosphate; the degreasing temperature is 40-80°C, and water bath heating is used; and the degreasing time is 2-10 min.
[0016] Furthermore, the degreased magnesium-lithium alloy sample is pickled to remove impurities and chemical oxide film on the surface of the magnesium-lithium alloy; the pickling step uses a mixed solution consisting of 5-100 g / L of organic acid and 0-50 g / L of sodium nitrate; the organic acid is selected from at least one of glacial acetic acid, oxalic acid, citric acid, and tartaric acid; the pickling temperature is 30-50°C, and water bath heating is used; the pickling time is 40-60s.
[0017] Furthermore, the pickled magnesium-lithium alloy sample is alkali washed to remove the pickling residue on the surface of the magnesium-lithium alloy; the alkali washing step uses a mixed solution consisting of 5-20 g / L sodium hydroxide, 0-10 / L sodium tripolyphosphate and 0-1 g / L sodium dodecyl sulfate; the alkali washing temperature is 50-70°C, and water bath heating is used; the alkali washing time is 40-60 s.
[0018] Furthermore, the cleaning in step S30 is specifically: using anhydrous ethanol for ultrasonic cleaning, and then rinsing with deionized water, and the time of the anhydrous ethanol ultrasonic cleaning is 3 to 15 minutes.
[0019] The present invention has the following beneficial effects: The method for preparing a magnesium-lithium alloy plasma electrolytic oxidation film layer in a pure ionic liquid of the present invention can effectively improve the corrosion resistance of the magnesium-lithium alloy by performing plasma electrolytic oxidation treatment in a non-aqueous electrolyte; using a pure ionic liquid as an electrolyte can significantly reduce the working voltage of the plasma electrolytic oxidation, thereby improving energy efficiency, because the pure ionic liquid has excellent electrical conductivity and electrochemical stability, and can achieve an effective oxidation reaction at a lower voltage; the electrolyte uses a pure ionic liquid, such as 1-butyl-3-methylimidazolium tetrafluoroborate, which can promote the formation of a uniform and dense film layer on the surface of the magnesium-lithium alloy, and the film layer does not have pores and has high corrosion resistance, and can effectively prevent the penetration of corrosive media; using a pure ionic liquid as an electrolyte, the ionic liquid is uniformly adsorbed on the surface of the substrate in the initial stage of the plasma electrolytic oxidation process to form a corrosion inhibition layer, resulting in uniform discharge on the surface of the substrate during the entire plasma electrolytic oxidation process, thereby reducing the surface roughness; the etc. prepared using the pure ionic liquid The plasma electrolytic oxidation film has improved corrosion resistance, which is attributed to the fact that the film prepared by plasma electrolytic oxidation in pure ionic liquid has no pores, no corrosion channels, and it is difficult for corrosive media to penetrate. In addition, when plasma electrolytic oxidation is carried out in pure ionic liquid, the substrate discharge is uniform and the surface roughness of the formed film is reduced. When plasma electrolytic oxidation is carried out in traditional aqueous solution, water will affect the generation of plasma discharge, discharge behavior and film growth process, and the generated oxide film has a complex phase composition, mainly oxides, and there are many micropores and microcracks in the film. Compared with traditional aqueous electrolytes, pure ionic liquids have better environmental compatibility, are not easy to volatilize, and have less impact on the environment and operators. Plasma electrolytic oxidation using pure ionic liquid as electrolyte breaks the limitations of high-temperature molten salt system and realizes non-aqueous electrolyte plasma electrolytic oxidation under low temperature conditions. The electrolyte has a simple composition and strong conductivity, which can improve current efficiency and oxidation rate. The prepared film is uniform, dense, delicate and smooth, and has strong bonding with the substrate.
[0020] The present invention uses a magnesium-lithium alloy with extremely low density as a matrix and prepares a plasma electrolytic oxidation film on the surface of the matrix. The prepared film has a single component and the formed film microstructure is different from the typical porous morphology of a traditional plasma electrolytic oxidation film. The film prepared in a pure ionic liquid has local tiny protrusions but no porous structure.
[0021] Adding corrosion inhibitors to pure ionic liquid electrolytes can further improve metal corrosion resistance. The magnesium-lithium alloy plasma electrolytic oxide film with excellent corrosion resistance can further expand the application of magnesium-lithium alloys in 3C, medical equipment, aerospace and other fields. Compared with existing metal materials such as aluminum, nickel, titanium and stainless steel and their alloys, it can greatly reduce the weight of the product.
[0022] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings: Figure 1 The surface microscopic morphology scanning electron microscope image and energy spectrum analysis of the magnesium-lithium alloy plasma electrolytic oxide film layer prepared in Example 1 of the present invention; Figure 2 The cross-sectional microscopic morphology scanning electron microscope image and element distribution energy spectrum image of the magnesium-lithium alloy plasma electrolytic oxide film layer prepared in Example 1 of the present invention; Figure 3 This is the XRD phase diagram of the magnesium-lithium alloy plasma electrolytic oxide film prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The following embodiments of the present invention are described in detail with reference to the accompanying drawings, but the present invention can be implemented in a variety of different ways as defined and covered below. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.
[0025] The preparation method of the magnesium-lithium alloy plasma electrolytic oxidation film layer in the pure ionic liquid of this embodiment comprises the following steps: S100, subjecting the magnesium-lithium alloy sample to plasma electrolytic oxidation surface treatment, using the magnesium-lithium alloy sample as an anode, stainless steel, graphite or titanium as a cathode, and pure ionic liquid as a plasma electrolytic oxidation electrolyte, and adopting a constant current mode to perform plasma electrolytic oxidation under a normal temperature non-aqueous electrolyte. The pure ionic liquid is a commercially available ionic liquid with a purity of >97%.
[0026] Ionic liquids are generally composed of organic cations and inorganic anions. They are liquid salts at low temperatures (<100°C), also known as low-temperature molten salts. Due to their adsorption capacity on metal surfaces and their excellent properties such as low volatility, non-flammability, non-toxicity, high thermal stability and chemical stability, they are considered to be green and sustainable corrosion inhibitors. At present, ionic liquids have been widely used in electroplating. Electroplating in pure ionic liquids or in electroplating solutions based on ionic liquids can achieve non-aqueous electrolyte electroplating under low temperature conditions, improve current efficiency and deposition rate, and the prepared electroplated layer is uniform, dense, delicate and flat, and has strong bonding with the substrate. In addition, the wide liquid temperature range of ionic liquids is also conducive to increasing the rate of nucleation, surface diffusion, crystallization and other phenomena closely related to the deposition process at high temperatures, and the ductility and wear resistance of the obtained electroplated layer are enhanced. At present, a variety of metals can be deposited using ionic liquid electrodeposition technology. However, there are few studies on plasma electrolytic oxidation in pure ionic liquids and non-aqueous electrolytes based on ionic liquids, and there are almost no related reports at home and abroad, which is a technical gap in this field.
[0027] The method for preparing a magnesium-lithium alloy plasma electrolytic oxidation film layer in a pure ionic liquid of the present invention can effectively improve the corrosion resistance of the magnesium-lithium alloy by performing plasma electrolytic oxidation treatment in a non-aqueous electrolyte; using a pure ionic liquid as an electrolyte can significantly reduce the working voltage of the plasma electrolytic oxidation, thereby improving energy efficiency, because the pure ionic liquid has excellent electrical conductivity and electrochemical stability, and can achieve an effective oxidation reaction at a lower voltage; the electrolyte uses a pure ionic liquid, such as 1-butyl-3-methylimidazolium tetrafluoroborate, which can promote the formation of a uniform and dense film layer on the surface of the magnesium-lithium alloy, and the film layer does not have pores and has high corrosion resistance, and can effectively prevent the penetration of corrosive media; using a pure ionic liquid as an electrolyte, the ionic liquid is uniformly adsorbed on the surface of the substrate in the initial stage of the plasma electrolytic oxidation process to form a corrosion inhibition layer, resulting in uniform discharge on the surface of the substrate during the entire plasma electrolytic oxidation process, thereby reducing the surface roughness; the etc. prepared using the pure ionic liquid The plasma electrolytic oxidation film has improved corrosion resistance, which is attributed to the fact that the film prepared by plasma electrolytic oxidation in pure ionic liquid has no pores, no corrosion channels, and it is difficult for corrosive media to penetrate. In addition, when plasma electrolytic oxidation is carried out in pure ionic liquid, the substrate discharge is uniform and the surface roughness of the formed film is reduced. When plasma electrolytic oxidation is carried out in traditional aqueous solution, water will affect the generation of plasma discharge, discharge behavior and film growth process, and the generated oxide film has a complex phase composition, mainly oxides, and there are many micropores and microcracks in the film. Compared with traditional aqueous electrolytes, pure ionic liquids have better environmental compatibility, are not easy to volatilize, and have less impact on the environment and operators. Plasma electrolytic oxidation using pure ionic liquid as electrolyte breaks the limitations of high-temperature molten salt system and realizes non-aqueous electrolyte plasma electrolytic oxidation under low temperature conditions. The electrolyte has a simple composition and strong conductivity, which can improve current efficiency and oxidation rate. The prepared film is uniform, dense, delicate and smooth, and has strong bonding with the substrate.
[0028] The present invention uses a magnesium-lithium alloy with extremely low density as a matrix and prepares a plasma electrolytic oxidation film on the surface of the matrix. The prepared film has a single component and the formed film microstructure is different from the typical porous morphology of a traditional plasma electrolytic oxidation film. The film prepared in a pure ionic liquid has local tiny protrusions but no porous structure.
[0029] In this embodiment, the pure ionic liquid is one of 1,3-dimethylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butylimidazolium tetrafluoroborate, and N-butylimidazolium. In the plasma electrolytic oxidation process, different pure ionic liquids as electrolytes will have different effects on the surface treatment effect of magnesium-lithium alloy. 1,3-Dimethylimidazolium tetrafluoroborate (MMImBF4) has lower viscosity and higher conductivity, and its ion size is small, which helps to form a uniform oxide film on the surface of magnesium-lithium alloy and provide a more delicate film structure, thereby improving the density and corrosion resistance of the film. 1-Ethyl-3-methylimidazolium tetrafluoroborate (EMImBF4) has good electrochemical stability, which helps to form an oxide film with good electrochemical properties on the surface of magnesium-lithium alloy and enhance the adhesion and stability of the film. 1-Butyl-3-methylimidazolium tetrafluoroborate (BMImBF4) can be uniformly adsorbed on the substrate surface in the initial stage of the plasma electrolytic oxidation process to form a corrosion inhibition layer, resulting in consistent discharge on the substrate surface during the entire plasma electrolytic oxidation process, thereby reducing the surface roughness. This ionic liquid helps to improve the uniformity and corrosion resistance of the film layer. 1-Butyl imidazolium tetrafluoroborate, this ionic liquid, due to its longer alkyl chain, is adsorbed in the film layer, which helps to increase the contact angle of the film layer, thereby improving the corrosion resistance and durability of the film layer. N-butyl imidazole, whose cation has a long alkyl chain, helps to form a dense and stable oxide film on the surface of magnesium-lithium alloy, thereby improving the protective effect of the film layer. The selection of different pure ionic liquids is mainly based on their physical and chemical properties, such as viscosity, conductivity, ion size and alkyl chain length, which will affect the formation and performance of the film layer during plasma electrolytic oxidation. By optimizing the selection and use conditions of ionic liquids, the corrosion resistance and other surface properties of magnesium-lithium alloys can be effectively improved.
[0030] In this embodiment, a corrosion inhibitor suitable for magnesium-lithium alloy is added to the plasma electrolytic oxidation electrolyte. After the corrosion inhibitor is added, to prevent uneven dissolution of the corrosion inhibitor, the plasma electrolytic oxidation electrolyte is placed in a stirring state or an ultrasonic state until the corrosion inhibitor is completely dissolved.
[0031] In this embodiment, the corrosion inhibitor is at least one of azole compounds (such as benzotriazole, BTA), organic phosphates (such as 2-hydroxyphosphonoacetic acid, HPA), and rare earth salts (such as cerium salts). Adding a corrosion inhibitor to the plasma electrolytic oxidation electrolyte can effectively improve the corrosion resistance of magnesium-lithium alloys. Different corrosion inhibitors have different effects: azole compounds, such corrosion inhibitors usually have good film-forming ability and adsorption properties. For example, in the study of the corrosion inhibition performance of carbon steel in hydrochloric acid solution, the static weight loss method found that its optimal corrosion inhibition rate can reach 99.37%. Organic phosphates usually have good chemical stability and thermal stability, and are suitable for high temperature and harsh environments; by interacting with the metal surface and doping into the film layer, they can effectively isolate the corrosive medium and reduce the corrosion of the metal. Rare earth salts, rare earth elements have a special electronic structure and can provide additional chemical stability. As corrosion inhibitors, they are doped into the film layer to enhance the protective effect of the surface of magnesium-lithium alloys. In practical applications, the selection of corrosion inhibitors needs to consider their compatibility with magnesium-lithium alloys, environmental conditions, cost-effectiveness, and impact on the environment. The corrosion resistance of magnesium-lithium alloys can be further improved by optimizing the type and concentration of corrosion inhibitors and promoting the dissolution and dispersion of corrosion inhibitors by stirring or ultrasound.
[0032] In this embodiment, the process parameters of plasma electrolytic oxidation in step S100 are: using constant current mode, keeping the temperature below 40°C, plasma electrolytic oxidation time of 10 to 30 minutes, frequency of 600 to 1000 Hz, and forward duty cycle of 12% to 20%. In the process of plasma electrolytic oxidation, the optimization of process parameters is crucial to the formation of high-quality oxide film layers. A constant current mode is adopted. In the constant current mode, the current is kept constant, which helps to control the growth rate and uniformity of the oxide film. The film layer prepared in this mode usually has good density and fewer defects. The temperature is below 40°C. Maintaining a low processing temperature helps to avoid excessive thermal damage to the film layer and ensure the uniformity and adhesion of the film layer. Excessive temperature may cause damage to the film layer structure and performance degradation. The oxidation time is 10 to 30 minutes. The oxidation time has a direct impact on the thickness and density of the film layer. The appropriate oxidation time can ensure that the film layer reaches the required thickness and good protective performance. Too short a time may cause the film layer to be uneven or too thin, while too long a time may cause the film layer to grow excessively and have a loose structure. The frequency is 600-1000Hz. The choice of frequency will affect the uniformity of discharge and the growth rate of the film layer. Within this frequency range, the uniform growth of the film layer can be promoted and good corrosion resistance can be obtained. Too low a frequency may lead to uneven discharge, while too high a frequency may increase energy consumption and cause the surface of the film layer to be rough. The forward duty cycle is 12%-20%. The duty cycle affects the duration and energy distribution of the discharge. An appropriate duty cycle helps to form a uniform and dense oxide film. Too low a duty cycle may lead to insufficient film growth, while too high a duty cycle may increase energy consumption and affect the uniformity of the film layer. Optimized process parameters are crucial to obtaining high-quality plasma electrolysis films. By precisely controlling these parameters, the uniformity, density and corrosion resistance of the film layer can be ensured, thereby improving the overall performance and application range of magnesium-lithium alloys.
[0033] In this embodiment, a pre-treatment step is also included before step S100, specifically: S10, grinding the surface of the magnesium-lithium alloy sample until it is smooth and free of impurities; S20, degreasing the polished magnesium-lithium alloy sample to remove oil stains on the surface of the magnesium-lithium alloy sample; S30, cleaning the surface of the magnesium-lithium alloy sample and drying it. Through step S10, the surface of the magnesium-lithium alloy sample is polished until it is smooth and free of impurities, and the surface oxide layer, corrosion products, burrs, impurities, etc. are removed by physical methods to ensure that the surface of the sample is smooth and clean, thereby improving the quality of subsequent plasma electrolytic oxidation treatment and the adhesion between the film layer and the substrate. Grinding can also create surface conditions that are conducive to the uniform growth of the oxide film. Optionally, the grinding sandpaper uses 180-1500 mesh SiC sandpaper, and alternately grinds in two vertical directions until the surface is smooth and free of impurities. Through step S20, the polished magnesium-lithium alloy sample is degreased to remove oil stains on the surface of the magnesium-lithium alloy sample. The degreasing step is to remove grease and pollutants attached to the surface. These substances may interfere with the subsequent plasma electrolytic oxidation process, resulting in decreased adhesion of the film layer and uneven film quality. Degreasing ensures the consistency of the chemical state of the sample surface and provides a clean surface for forming a uniform and dense oxide film. Step S30 is used to clean and dry the surface of the magnesium-lithium alloy sample to further remove tiny particles, salts and other contaminants that may remain on the surface. Drying after cleaning ensures that there are no impurities or other components that affect subsequent processes on the surface. The dry surface is to prevent the residual aqueous solution on the surface of the magnesium-lithium alloy from reacting with the matrix to affect the surface, which helps to obtain uniform discharge and high-quality oxide film. These pre-treatment steps together ensure that the surface of the magnesium-lithium alloy sample is in the best condition, providing a good foundation for plasma electrolytic oxidation, so that a uniform, dense, and highly adhesive oxide film can be formed, improving the corrosion resistance and wear resistance of the magnesium-lithium alloy. These steps are crucial to ultimately obtaining a high-performance surface treatment layer.
[0034] In this embodiment, the process parameters of degreasing in step S20 are: the degreasing solution is a mixed solution composed of 2-50 g / L sodium hydroxide, 0-20 g / L sodium silicate, 1-10 g / L sodium carbonate, and 0-30 g / L sodium phosphate; the degreasing temperature is 40-80 ° C, and water bath heating is used; the degreasing time is 2-10 min. Sodium hydroxide (2-50 g / L), as a strong base, helps to saponify grease and improve degreasing efficiency. Too low a concentration may not effectively remove grease, while too high a concentration may cause material corrosion or excessive chemical foam. Sodium silicate (0-20 g / L), as an auxiliary agent, can improve the alkalinity and emulsification ability of the solution and help remove grease, but too high a concentration will increase the cost and have a potential corrosive effect on the equipment. Sodium carbonate (1-10 g / L) enhances the buffering capacity and emulsification of the solution and helps remove grease. Too low a concentration may affect the degreasing effect, while too high a concentration may cause solution stability problems. Sodium phosphate (0-30 g / L) improves the emulsification and dispersibility of the solution and helps remove grease, but high concentrations may increase costs and burden the environment. Too low a concentration of the degreasing solution may result in incomplete degreasing and grease residue. Degreasing temperature (40-80 ° C) Increased temperature helps dissolve and emulsify grease and improves degreasing efficiency, but too high a temperature may cause the decomposition of certain components in the solution, affect the stability of the degreasing solution, increase energy consumption, and may cause corrosion or damage to the material. Too low a degreasing temperature may affect the degreasing efficiency. Degreasing time (2-10 min) Appropriate degreasing time ensures that the grease is fully reacted and removed. Too short a time may result in incomplete degreasing, and too long a time may cause excessive corrosion or damage to the alloy surface. Water bath heating Water bath heating provides a gentle and uniform heating method, which helps control the reaction temperature and prevent local overheating, but if the water bath temperature is not properly controlled, it may result in poor degreasing effect or material damage. The selection of degreasing process parameters has an important influence on the surface cleanliness and subsequent processing quality of magnesium-lithium alloys. Reasonable parameter settings can ensure the degreasing effect and avoid possible defects, thereby improving the overall performance of magnesium-lithium alloys.
[0035] In this embodiment, the degreased magnesium-lithium alloy sample is pickled to remove impurities and chemical oxide films on the surface of the magnesium-lithium alloy; the pickling step uses a mixed solution consisting of 5-100g / L organic acid and 0-50g / L sodium nitrate; the organic acid is selected from at least one of glacial acetic acid, oxalic acid, citric acid, and tartaric acid; the pickling temperature is 30-50°C, and water bath heating is used; the pickling time is 40-60s. Organic acid can effectively remove oxides and rust on the metal surface. The concentration of organic acid within an appropriate range can ensure the pickling effect and avoid excessive corrosion. Too low a concentration may not effectively remove the oxide scale, while too high a concentration may cause excessive corrosion and affect the performance of the material. The concentration of sodium nitrate (0-50g / L) can increase the oxidation potential of the pickling solution, help remove stubborn oxide scales, and inhibit the generation of hydrogen to a certain extent, reducing the risk of hydrogen embrittlement. Too high a concentration of sodium nitrate may increase costs and may pose risks to the environment and the health of operators. Pickling temperature (30-50°C), within the appropriate temperature range, the pickling solution has a high reactivity and can effectively remove the oxide scale while avoiding rapid corrosion caused by excessively high temperature. Too low a temperature may slow down the pickling speed and result in poor results. Too high a temperature may accelerate corrosion and even cause thermal damage to the material. Pickling time (40-60s), appropriate pickling time can ensure that the metal surface reacts fully, removes the oxide scale, and avoids excessive corrosion. Too short a pickling time may not completely remove the oxide scale, while too long a time may cause excessive corrosion of the material. Water bath heating, water bath heating can provide uniform temperature control, which helps the stability and repeatability of the pickling process. If the water bath temperature is not properly controlled, uneven pickling results or material damage may occur. The selection of pickling process parameters has an important influence on the surface treatment quality of magnesium-lithium alloys. Reasonable parameter settings can ensure the pickling effect and avoid possible defects, thereby improving the overall performance of magnesium-lithium alloys.
[0036] In this embodiment, the pickled magnesium-lithium alloy sample is alkali washed to remove the pickling residue on the surface of the magnesium-lithium alloy; the alkali washing step uses a mixed solution composed of 5-20g / L sodium hydroxide, 0-10 / L sodium tripolyphosphate and 0-1g / L sodium dodecyl sulfate; the alkali washing temperature is 50-70°C, and water bath heating is used; the alkali washing time is 40-60s. The concentration of sodium hydroxide (5-20g / L), sodium hydroxide as a strong base, can effectively neutralize the pickling solution remaining on the surface of the magnesium-lithium alloy. Within the appropriate concentration range, the alkali washing effect can be guaranteed while avoiding excessive corrosion to the alloy matrix. The concentration of sodium tripolyphosphate (0-10g / L), sodium tripolyphosphate has the ability to chelate metal ions, can prevent gelation and precipitation caused by metal ions, and helps to maintain the uniformity and stability of the solution. In addition, it can also provide a certain buffering effect to reduce the corrosiveness of sodium hydroxide. Too high a concentration may increase the processing cost and may form residues that are difficult to clean on the surface of the magnesium-lithium alloy, affecting the quality of subsequent processes. The concentration of sodium dodecyl sulfate (0-1g / L) is a surfactant that can enhance the wettability and permeability of the solution, helping sodium hydroxide and sodium tripolyphosphate to better contact and clean the surface of the magnesium-lithium alloy. Too high a concentration may produce too much foam, affecting the cleaning effect, and may also increase the risk of residues after cleaning. The alkali washing temperature (50-70°C) can increase the rate of chemical reactions, shorten the alkali washing time, and improve production efficiency within an appropriate temperature range. Too low a temperature may not achieve the ideal cleaning effect, while too high a temperature may accelerate the corrosion of sodium hydroxide on the magnesium-lithium alloy. The alkali washing time (40-60s) is an appropriate alkali washing time to ensure that the alloy surface is fully cleaned and the residual pickling solution is removed. If the time is too short, the cleaning may not be thorough, affecting the quality of the subsequent process; if the time is too long, it may cause excessive corrosion and cause unnecessary damage to the alloy surface. Water bath heating, water bath heating can provide uniform temperature control, which helps the stability and repeatability of the alkali washing process. If the water bath temperature is not properly controlled, it may cause uneven alkali washing or material damage. The selection of alkali washing process parameters has an important influence on the surface treatment quality of magnesium-lithium alloys. Reasonable parameter settings can ensure the alkaline washing effect and avoid possible defects, thereby improving the overall performance of magnesium-lithium alloys.
[0037] In this embodiment, the cleaning in step S30 is specifically: ultrasonic cleaning with anhydrous ethanol, and then rinsing with deionized water, and the time of ultrasonic cleaning with anhydrous ethanol is 3 to 15 minutes. During the ultrasonic cleaning time of 3 to 15 minutes, anhydrous ethanol can effectively dissolve and remove organic residues on the surface of magnesium-lithium alloy, such as grease, dirt and other organic matter. The effect of ultrasound can enhance the cleaning effect, and the explosive force of tiny bubbles generated by the cavitation effect can further loosen and remove surface pollutants. The appropriate cleaning time can ensure that the alloy surface is fully contacted with the cleaning liquid, remove the residual processing and treatment solution, prepare for the subsequent process steps, and avoid excessive corrosion or damage to the alloy surface; if the cleaning time is less than 3 minutes, the organic residues and pollutants on the surface may not be completely removed, resulting in quality problems in the subsequent process, such as insufficient film adhesion or uneven surface treatment; a cleaning time exceeding 15 minutes may cause excessive volatilization of anhydrous ethanol, increase safety risks, and may also cause changes in the microstructure of the surface of the magnesium-lithium alloy due to the long-term action of ultrasound, causing unnecessary surface damage. The effect of deionized water rinsing is to remove the ethanol and other dissolved impurities that may remain after the anhydrous ethanol ultrasonic cleaning, ensuring that the surface of the magnesium-lithium alloy reaches the required cleanliness. The use of deionized water can prevent the ions in the tap water from affecting subsequent processes, such as ion contamination or corrosion. Anhydrous ethanol ultrasonic cleaning combined with deionized water rinsing is an effective cleaning method that can reduce potential damage to the surface of the magnesium-lithium alloy while ensuring the cleaning effect. Control of the cleaning time is crucial to ensure the cleaning quality.
[0038] Example 1 A method for preparing a magnesium-lithium alloy plasma electrolytic oxide film layer in a pure ionic liquid comprises the following steps: 1) Mechanical grinding A magnesium-lithium alloy with a size of 20mm × 20mm × 3mm was used as the substrate, and SiC sandpapers of 180 mesh, 400 mesh, 800 mesh, 1000 mesh, and 1500 mesh were used to grind the surface step by step until it was smooth and flat. After grinding, anhydrous ethanol was ultrasonicated for 5 minutes, and the surface was washed with deionized water and dried. 2) Degreasing The mechanically polished magnesium-lithium alloy specimens were immersed in a degreasing solution at 60°C for 5 minutes; wherein the degreasing solution was a mixture of 30 g / L sodium hydroxide, 10 g / L sodium silicate, 5 g / L sodium carbonate, and 10 g / L sodium phosphate. After degreasing, they were first rinsed with hot water and then with cold water.
[0039] 3) Pickling The magnesium-lithium alloy sample after cold water washing was immersed in an acidic liquid at room temperature for 30 seconds; wherein the acidic liquid was a mixture of 50g / L glacial acetic acid and 30g / L sodium nitrate. After acid washing, it was rinsed with tap water, followed by deionized water, and finally dried with cold air.
[0040] 4) Alkaline washing The magnesium-lithium alloy sample after cold water washing was immersed in 5g / L sodium hydroxide at 60°C for 3min. After alkaline washing, it was first rinsed with hot water and then rinsed with cold water.
[0041] 5) Plasma electrolytic oxidation 1-Butyl-3-methylimidazolium tetrafluoroborate was used as the electrolyte and placed in a circulating water cooling system. A magnesium-lithium alloy sample was used as the anode and stainless steel was used as the cathode. The plasma electrolytic oxidation was carried out in a constant current mode. The current in the constant current mode was set to 0.3A, the distance between the anode and the cathode was controlled at 10cm, the positive and negative duty cycles were both 10%, the forward frequency was set to 200Hz, the plasma electrolytic oxidation time was 15min, and the temperature was 15℃. After the plasma electrolytic oxidation was completed, the sample was ultrasonically cleaned with anhydrous ethanol, dried with hot air, placed in a vacuum drying oven, and dried at 50℃ to obtain a magnesium-lithium alloy plasma electrolytic oxidation sample.
[0042] See also Figure 1 (a) It can be seen that the magnesium-lithium alloy plasma electrolytic oxide film prepared in this embodiment is different from the typical porous morphology of the plasma electrolytic oxide film prepared in the traditional aqueous solution from a microscopic point of view. There are tiny protrusions on the surface of the film, and the film is relatively flat, dense and uniform. The measured surface roughness is only 0.442μm (Ra). Figure 1 As can be seen in (b), four elements, C, O, F and Mg, were detected on the surface of the film. The C, O and F elements originated from the ionic liquid, while Mg originated from the matrix.
[0043] See also Figure 2 As shown in Table 1, for the magnesium-lithium alloy plasma electrolytic oxidation film layer in the pure ionic liquid prepared in this embodiment, the film thickness was measured at 5 different positions, and the film thickness was about 9.45μm, and the film layer mainly contained O, F, and Mg elements. From the film thickness measured at different positions in the table, it can be seen that the film thickness error value is less than 1.33μm. This is because the ionic liquid is uniformly adsorbed on the surface of the substrate in the initial stage of plasma electrolytic oxidation, which makes the substrate uniformly discharged and the surface roughness of the film layer is reduced, so the film thickness is uniform. Moderate thickness can not only ensure that the film layer is uniform and dense, with low surface roughness, but also provide better protection for the film layer and provide an effective barrier for the substrate material.
[0044] Table 1
[0045] See also Figure 3 It can be seen that the main phases of the film layer are MgF2, MgC2 and Mg(BF4)2, and Mg and Li are matrix phases. Since the film layer is thin, X-rays pass through the film layer, so the matrix phase is detected.
[0046] By using plasma electrolytic oxidation technology in pure ionic liquid to prepare magnesium-lithium alloy film layers, a microstructure and performance different from the traditional aqueous solution method is achieved. The film layer obtained by the method of the present invention has the following significant beneficial effects: The surface morphology is improved. Compared with the porous plasma electrolytic oxide film prepared in the conventional aqueous solution, the film prepared in this embodiment has tiny protrusions on the surface, and is smoother, denser and more uniform overall. This improved surface morphology helps to improve the corrosion resistance and wear resistance of the film, while reducing the penetration path of the corrosive medium.
[0047] Low surface roughness, the measured surface roughness is only 0.442μm (Ra). This low surface roughness value helps to reduce the surface friction coefficient and improve the performance of magnesium-lithium alloy in various application environments. For example, in the aerospace field, it can reduce air resistance and improve flight efficiency.
[0048] The elements are evenly distributed. The four elements C, O, F and Mg detected on the surface of the film are evenly distributed, of which C, O and F come from the ionic liquid, while Mg comes from the matrix. This uniform element distribution helps to improve the chemical stability and physical properties of the film.
[0049] The film layer has a moderate thickness of about 9.45 μm, which can provide sufficient protection without excessively increasing the weight of the material or changing its mechanical properties, thus maintaining the lightweight characteristics of magnesium-lithium alloy.
[0050] Stability of main phases: the film layer is mainly composed of stable phases such as MgF2, MgC2 and Mg(BF4)2. The presence of these phases helps to improve the corrosion resistance and chemical resistance of the film layer, and also enhances the hardness and wear resistance of the film layer.
[0051] Protection of the matrix phase. Since the film layer is thin, X-rays can pass through the film layer to detect the matrix phase, which shows that the film layer does not have a negative impact on the bulk properties of the matrix material, but instead forms an effective protective layer on its surface.
[0052] This embodiment successfully prepared a magnesium-lithium alloy film layer with excellent surface morphology, uniform element distribution, moderate thickness and stable phase by using plasma electrolytic oxidation technology in pure ionic liquid. These characteristics enable the film layer to show significant beneficial effects in improving corrosion resistance and wear resistance.
[0053] Example 2 A method for preparing a magnesium-lithium alloy plasma electrolytic oxide film layer in a pure ionic liquid comprises the following steps: 1) Mechanical grinding This step is the same as step 1 in Example 1; 2) Degreasing This step is the same as step 1 in Example 1; 3) Pickling This step is the same as step 1 in Example 1; 4) Alkaline washing This step is the same as step 1 in Example 1; 5) Plasma electrolytic oxidation 1-Butyl-3-methylimidazolium tetrafluoroborate was used as the electrolyte, 5g / L cerium nitrate hexahydrate was added as a corrosion inhibitor to the electrolyte, and the electrolyte was placed in a circulating water cooling system. The magnesium-lithium alloy sample was used as the anode, and stainless steel was used as the cathode. The plasma electrolytic oxidation was carried out in a constant current mode. The current in the constant current mode was set to 0.3A, the distance between the anode and the cathode was controlled at 10cm, the positive and negative duty cycles were both 10%, the forward frequency was set to 200Hz, the plasma electrolytic oxidation time was 15min, and the temperature was 15℃. After the plasma electrolytic oxidation was completed, the sample was ultrasonically cleaned with anhydrous ethanol, dried with hot air, placed in a vacuum drying oven, and dried at 50℃ to obtain a magnesium-lithium alloy plasma electrolytic oxidation sample.
[0054] Example 3 A method for preparing a magnesium-lithium alloy plasma electrolytic oxide film layer in a pure ionic liquid comprises the following steps: 1) Mechanical grinding This step is the same as step 1 in Example 1; 2) Degreasing This step is the same as step 1 in Example 1; 3) Pickling This step is the same as step 1 in Example 1; 4) Alkaline washing This step is the same as step 1 in Example 1; 5) Plasma electrolytic oxidation 1,3-dimethyl imidazole tetrafluoroborate was used as the electrolyte and placed in a circulating water cooling system. The magnesium-lithium alloy sample was used as the anode and stainless steel was used as the cathode. The plasma electrolytic oxidation was carried out in a constant current mode. The current in the constant current mode was set to 0.3A, the distance between the anode and the cathode was controlled at 10cm, the positive and negative duty ratios were both 10%, the forward frequency was set to 200Hz, the plasma electrolytic oxidation time was 15min, and the temperature was 15℃. After the plasma electrolytic oxidation was completed, the sample was ultrasonically cleaned with anhydrous ethanol, dried with hot air, placed in a vacuum drying oven, and dried at 50℃ to obtain a magnesium-lithium alloy plasma electrolytic oxidation sample.
[0055] Example 4 A method for preparing a magnesium-lithium alloy plasma electrolytic oxide film layer in a pure ionic liquid comprises the following steps: 1) Mechanical grinding This step is the same as step 1 in Example 1; 2) Degreasing This step is the same as step 1 in Example 1; 3) Pickling This step is the same as step 1 in Example 1; 4) Alkaline washing This step is the same as step 1 in Example 1; 5) Plasma electrolytic oxidation 1-Butyl imidazole tetrafluoroborate was used as the electrolyte and placed in a circulating water cooling system. A magnesium-lithium alloy sample was used as the anode and stainless steel was used as the cathode. The plasma electrolytic oxidation was carried out in a constant current mode. The current in the constant current mode was set to 0.3A, the distance between the anode and the cathode was controlled at 10cm, the positive and negative duty cycles were both 10%, the forward frequency was set to 200Hz, the plasma electrolytic oxidation time was 15min, and the temperature was 15℃. After the plasma electrolytic oxidation was completed, the sample was ultrasonically cleaned with anhydrous ethanol, dried with hot air, placed in a vacuum drying oven, and dried at 50℃ to obtain a magnesium-lithium alloy plasma electrolytic oxidation sample.
[0056] Example 5 A method for preparing a magnesium-lithium alloy plasma electrolytic oxide film layer in a pure ionic liquid comprises the following steps: 1) Mechanical grinding This step is the same as step 1 in Example 1; 2) Degreasing This step is the same as step 1 in Example 1; 3) Pickling This step is the same as step 1 in Example 1; 4) Alkaline washing This step is the same as step 1 in Example 1; 5) Plasma electrolytic oxidation 1-Butyl imidazole tetrafluoroborate was used as the electrolyte, 5g / L benzotriazole was added as a corrosion inhibitor to the electrolyte, and the electrolyte was placed in a circulating water cooling system. The magnesium-lithium alloy sample was used as the anode, and stainless steel was used as the cathode. The plasma electrolytic oxidation was carried out in a constant current mode. The current in the constant current mode was set to 0.3A, the distance between the anode and the cathode was controlled at 10cm, the positive and negative duty cycles were both 10%, the forward frequency was set to 200Hz, the plasma electrolytic oxidation time was 15min, and the temperature was 15℃. After the plasma electrolytic oxidation was completed, the sample was ultrasonically cleaned with anhydrous ethanol, dried with hot air, placed in a vacuum drying oven, and dried at 50℃ to obtain a magnesium-lithium alloy plasma electrolytic oxidation sample.
[0057] In summary: 1) The preparation method of the present invention uses pure ionic liquid to carry out plasma electrolytic oxidation directly on the magnesium-lithium alloy, and innovatively uses room temperature non-aqueous electrolyte for plasma electrolytic oxidation, breaking the limitations of the high-temperature molten salt system and realizing non-aqueous electrolyte plasma electrolytic oxidation under low temperature conditions. The electrolyte has a simple composition and strong conductivity, which can improve the current efficiency and oxidation rate. The prepared film layer is uniform, dense, fine and smooth, and has a strong bonding force with the substrate.
[0058] 2) The present invention uses magnesium-lithium alloy with extremely low density as the matrix, and prepares a plasma electrolytic oxide film on the surface of the matrix. The prepared film has a single component, and the formed film microstructure is different from the typical porous morphology of the traditional plasma electrolytic oxide film. The film prepared in pure ionic liquid has local tiny protrusions, but no porous structure. Adding corrosion inhibitors to the pure ionic liquid electrolyte further improves the corrosion resistance of the metal. The magnesium-lithium alloy plasma electrolytic oxide film with excellent corrosion resistance can further expand the application of magnesium-lithium alloy in 3C, medical equipment, aerospace and other fields, and can greatly reduce the weight of the product compared with existing metal materials such as aluminum, nickel, titanium and stainless steel and their alloys.
[0059] Matters not covered by the present invention are known technologies.
[0060] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0061] The above-mentioned embodiments only express several implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid, characterized in that: The following steps are involved: S100. The magnesium-lithium alloy sample is subjected to plasma electrolytic oxidation surface treatment. The magnesium-lithium alloy sample is used as the anode, stainless steel, graphite or titanium is used as the cathode, and pure ionic liquid is used as the plasma electrolytic oxidation electrolyte. The plasma electrolytic oxidation is carried out in a constant current mode under a non-aqueous electrolyte at room temperature.
2. The method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid according to claim 1, characterized in that: The pure ionic liquid is one of 1,3-dimethylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butylimidazolium tetrafluoroborate and N-butylimidazolium.
3. The method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid according to claim 1, characterized in that: A corrosion inhibitor suitable for magnesium-lithium alloy is added to the plasma electrolytic oxidation electrolyte. After the corrosion inhibitor is added, the plasma electrolytic oxidation electrolyte is placed in a stirring state or an ultrasonic state until the corrosion inhibitor is completely dissolved.
4. The method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid according to claim 3, characterized in that: The magnesium-lithium alloy corrosion inhibitor is at least one of azole compounds, organic phosphates, and rare earth salts.
5. The method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid according to any one of claims 1 to 4, characterized in that: The process parameters of the plasma electrolytic oxidation in step S100 are: The constant current mode is adopted, the temperature is maintained below 40°C, the plasma electrolytic oxidation time is 10 to 30 minutes, the frequency is 600 to 1000 Hz, and the forward duty cycle is 12% to 20%.
6. The method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid according to any one of claims 1 to 4, characterized in that: Before step S100, a pre-processing step is also included, specifically: S10. Grind the surface of the magnesium-lithium alloy sample until it is smooth and free of impurities; S20, degreasing the polished magnesium-lithium alloy sample to remove oil stains on the surface of the magnesium-lithium alloy sample; S30, clean the surface of the magnesium-lithium alloy sample and dry it.
7. The method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid according to claim 6, characterized in that: The process parameters for degreasing in step S20 are: The degreasing solution is a mixed solution composed of 2-50 g / L sodium hydroxide, 0-20 g / L sodium silicate, 1-10 g / L sodium carbonate, and 0-30 g / L sodium phosphate; The degreasing temperature is 40-80°C, heated in a water bath; The degreasing time is 2 to 10 minutes.
8. The method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid according to claim 7, characterized in that: The degreased magnesium-lithium alloy sample is pickled to remove impurities and chemical oxidation film on the surface of the magnesium-lithium alloy; The pickling solution is a mixed solution consisting of 5 to 100 g / L of organic acid and 0 to 50 g / L of sodium nitrate; The organic acid is selected from at least one of glacial acetic acid, oxalic acid, citric acid and tartaric acid; The pickling temperature is 30-50°C, heated in a water bath; The pickling time is 40 to 60 seconds.
9. The method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid according to claim 8, characterized in that: The pickled magnesium-lithium alloy sample is subjected to alkaline washing to remove the pickling residue on the surface of the magnesium-lithium alloy; The alkali washing step uses a mixed solution consisting of 5-20 g / L sodium hydroxide, 0-10 g / L sodium tripolyphosphate and 0-1 g / L sodium dodecyl sulfate; The alkali washing temperature is 50-70°C, heated in a water bath; The alkaline washing time is 40 to 60 seconds.
10. The method for preparing a magnesium-lithium alloy plasma electrolytic oxide film in a pure ionic liquid according to claim 6, characterized in that: The cleaning in step S30 is specifically as follows: Use anhydrous ethanol ultrasonic cleaning, then rinse with deionized water. The anhydrous ethanol ultrasonic cleaning time is 3 to 15 minutes.
